Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, ( x-1)3= -27
=> x - 1 = -3
=> x = -2
b, ( 2x - 1)2=25
=> 2x - 1 = 5 hoặc 2x - 1 = -5
=> 2x = 6 hoặc 2x = -4
=> x = 3 hoặc x = -2
c, ( x - 3/4)2= ( 1/2)6
=> (x - 3/4)^2 = 1/64
=> x - 3/4 = 1/8 hoặc x - 3/4 = -1/8
=> x = 7/8 hoặc x = 5/8
d, 2 x + 2 x +2 = 80
=> 2^x + 2^x.4 = 80
=> 2^x(1 + 4) = 80
=> 2^x.5 = 80
=> 2^x = 16
=> x = 4
e, 4x + 4 x + 3 = 4160
=> 4^x(1 + 64) = 4160
=> 4^x.65 = 4160
=> 4^x = 64
=> x = 3
Bài 2:
1. \(8^n:2^n=4\)
⇔ \(2^{3n}:2^n=2^2\)
⇔ \(2^{2n}=2^2\)
⇔ \(2n=2\)
⇔ \(n=2:2\)
⇒ \(n=1\)
Vậy \(n=1.\)
Chúc bạn học tốt!
1, \(\left(xy\right)^2-\frac{1}{2}x^2y^2+3xy^2.\left(-\frac{1}{3}x\right)\)
\(=x^2y^2-\frac{1}{2}x^2y^2-x^2y^2\)
\(=-\frac{1}{2}x^2y^2\)
2, \(4.\left(-\frac{1}{2}x\right)^2-\frac{3}{2}x.\left(-x\right)+\frac{1}{3}x^2\)
\(=x^2+\frac{3}{2}x^2+\frac{1}{3}x^2\)
\(=\frac{17}{6}x^2\)
3, \(-4.\left(2x\right)^2y^3+\frac{1}{2}xy.\left(-2xy^2\right)+\frac{1}{4}x^2y^3\)
\(=-16x^2y^3-x^2y^3+\frac{1}{4}x^2y^3\)
\(=-\frac{67}{4}x^2y^3\)
4, \(\frac{1}{3}x^4y-\frac{5}{3}x^3.\left(\frac{5}{2}xy\right)+\frac{3}{4}x^4y\)
\(=\frac{1}{3}x^4y-\frac{25}{6}x^4y+\frac{3}{5}x^4y\)
\(=-\frac{97}{30}x^4y\)
5, \(\left(-2x^3y^4\right)^2-5x^2y.\left(\frac{3}{4}x^4y^7\right)-\frac{2}{3}x^6y^8\)
\(=4x^6y^8-\frac{15}{4}x^6y^8-\frac{2}{3}x^6y^8\)
\(=-\frac{5}{12}x^6y^8\)
1.
\(-3x^5y^4+3x^2y^3-7x^2y^3+5x^5y^4\)
\(=(-3x^5y^4+5x^5y^4)+(3x^2y^3-7x^2y^3)\)
\(=2x^5y^4-4x^2y^3\)
2.
\(\frac{1}{2}x^4y-\frac{3}{2}x^3y^4+\frac{5}{3}x^4y-x^3y^4\)
\(=(\frac{1}{2}x^4y+\frac{5}{3}x^4y)-(\frac{3}{2}x^3y^4+x^3y^4)\)
\(=\frac{13}{6}x^4y-\frac{5}{2}x^3y^4\)
3.
\(5x-7xy^2+3x-\frac{1}{2}xy^2\)
\(=(5x+3x)-(7xy^2+\frac{1}{2}xy^2)\)
\(=8x-\frac{15}{2}xy^2\)
4.
\(\frac{-1}{5}x^4y^3+\frac{3}{4}x^2y-\frac{1}{2}x^2y+x^4y^3\)
\(=(\frac{-1}{5}x^4y^3+x^4y^3)+(\frac{3}{4}x^2y-\frac{1}{2}x^2y)\)
\(=\frac{4}{5}x^4y^3+\frac{1}{4}x^2y\)
5.
\(\frac{7}{4}x^5y^7-\frac{3}{2}x^2y^6+\frac{1}{5}x^5y^7+\frac{2}{3}x^2y^6\)
\(=(\frac{7}{4}x^5y^7+\frac{1}{5}x^5y^7)+(-\frac{3}{2}x^2y^6+\frac{2}{3}x^2y^6)\)
\(=\frac{39}{20}x^5y^7-\frac{5}{6}x^2y^6\)
6.
\(\frac{1}{3}x^2y^5(-\frac{3}{5}x^3y)+x^5y^6=(\frac{1}{3}.\frac{-3}{5})(x^2.x^3)(y^5.y)+x^5y^6\)
\(=\frac{-1}{5}x^5y^6+x^5y^6=\frac{4}{5}x^5y^6\)
Lời giải:
1.
\((-2x^4y^3z^7)^2(\frac{1}{4}xy^5)(-3x^2yz)^3(\frac{-1}{27}x^3yz^2)\)
\(=(4x^8y^6z^{14})(\frac{1}{4}xy^5)(-27x^6y^3z^3)(-\frac{1}{27}x^3yz^2)\)
\(=(4.\frac{1}{4}.-27.\frac{-1}{27})(x^8.x.x^6.x^3)(y^6.y^5.y^3.y)(z^{14}.z^3.z^2)\)
\(=x^{18}.y^{15}.z^{19}\)
2.
\(=(\frac{-1}{3}.\frac{4}{5}.\frac{-27}{10})(x.x^5.x^2)(y^2.y^6.y)(z.z.z^4)\)
\(=\frac{18}{25}.x^8.y^9.z^6\)
3.
\(=(49.x^{10}y^2z^4)(\frac{-1}{4}.x^3yz^7)(\frac{8}{21}x^5z^4)\)
\(=(49.\frac{-1}{4}.\frac{8}{21})(x^{10}.x^3.x^5)(y^2.y)(z^4.z^7.z^4)\)
\(=\frac{-14}{3}.x^{18}.y^3.z^{15}\)
4.
\(=(\frac{-1}{64}.x^8.y^9.z^{12})(4x^2y^2z^4)(\frac{-5}{3}x^4yz)\)
\(=(\frac{-1}{64}.4.\frac{-5}{3})(x^8.x^2.x^4)(y^9.y^2.y)(z^{12}.z^4.z)\)
\(=\frac{5}{48}.x^{14}.y^{12}.z^{17}\)
5.
\(=(\frac{1}{16}.x^8.y^4z^2)(-8xyz^2).(-\frac{1}{2}x^4yz)\)
\(=(\frac{1}{16}.-8.\frac{-1}{2})(x^8.x.x^4)(y^4.y.y)(z^2.z^2.z)\)
\(=\frac{1}{4}.x^{13}.y^6.z^5\)
a) \(\left(-2\right)^3+2^2+\left(-1\right)^{20}+\left(-2\right)^0\)
\(=-8+4+1+1=-2\)
b) \(\left(3^2\right)^2-\left(-5^2\right)^2+\left[\left(-2\right)^3\right]^2\)
\(=9^2-\left(-25\right)^2+\left(-8\right)^2\)
\(=81-625+64=-480\)
c) Bạn sửa lại đề!